The role of auditing in ensuring the quality of healthcare services: A literature review - Nadia Putri Untiami; Reynanda Sabrina; Assyifa Ramadhani; Acim Heri Iswanto (Indonesian Journal of Health Science, 2026)
Audits, as systematic evaluation tools, play a strategic role in ensuring and improving the quality of healthcare services. This literature review aims to analyze the contribution of audits—including clinical audits, operational audits, and information system audits—to service quality standards in healthcare facilities. The method used was a systematic literature review with a narrative synthesis approach of nine selected scientific articles published between 2016 and 2026. The results of the study indicate that ISO 9001:2015-based internal audits, operational audits, clinical coding audits, and Hospital Management Information System (HMIS) audits have a positive impact on service effectiveness, patient safety, and the accuracy of clinical data. Audit implementation still faces various obstacles, such as the high workload of healthcare personnel, limited human resource competencies, the perception of audits as an administrative burden, and limitations in information technology infrastructure. The conclusion of this study emphasizes that optimizing audits requires the integration of human resource capacity building, the development of reliable information systems, and a supportive organizational culture of quality. The application of the Plan-Do-Check-Act (PDCA) cycle is recommended as a framework to drive continuous improvement in service quality.